2021
DOI: 10.3390/molecules26175412
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Fresh Goji (Lycium barbarum L.) Berries from Two Cultivars Grown in Central Italy: A Multi-Methodological Approach

Abstract: The metabolite profile of fresh Goji berries from two cultivars, namely Big Lifeberry (BL) and Sweet Lifeberry (SL), grown in the Lazio region (Central Italy) and harvested at two different periods, August and October, corresponding at the beginning and the end of the maturation, was characterized by means of nuclear magnetic resonance (NMR) and electrospray ionization Fourier transform ion cyclotron resonance (ESI FT-ICR MS) methodologies. Several classes of compounds such as sugars, amino acids, organic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…For the untargeted NMR analysis, Bligh–Dyer extraction procedure was applied, following the previously described conditions [ 33 ]. The hydroalcoholic extract was dried and then solubilized with 0.75 mL of 400 mM phosphate buffer/D 2 O, containing a 1 mM 3-(trimethylsilyl)-propionic-2,2,3,3-d 4 acid sodium salt (TSP) as an internal standard, and then transferred into a 5 mm NMR tube.…”
Section: Methodsmentioning
confidence: 99%
“…For the untargeted NMR analysis, Bligh–Dyer extraction procedure was applied, following the previously described conditions [ 33 ]. The hydroalcoholic extract was dried and then solubilized with 0.75 mL of 400 mM phosphate buffer/D 2 O, containing a 1 mM 3-(trimethylsilyl)-propionic-2,2,3,3-d 4 acid sodium salt (TSP) as an internal standard, and then transferred into a 5 mm NMR tube.…”
Section: Methodsmentioning
confidence: 99%
“…The NMR analysis of the considered samples (including MRS broth as the blank) allows identifying two organic acids (lactate and formate), nine amino acids (alanine, valine, glycinebetaine, isoleucine, leucine, glycine, phenylalanine, tyrosine, and tryptophan), and choline by means of 2D experiments and literature data ( Di Matteo et al, 2021 ; Spano et al, 2021 ) as reported in Supplementary Table S1 and Supplementary Figures S2–S6 . Comparing the NMR results obtained in Table 2 , lactate and formate were identified among organic acids, whereas leucine, isoleucine, valine, alanine, glycine, tyrosine, phenylalanine, tyrosine, and tryptophan were revealed among amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…The ESI FT-ICR mass spectra of hydroalcoholic extracts showed peaks due to protonated compounds or alkali metal adducts for positive polarity mode and deprotonated species or chloride adducts for negative polarity mode. This method has been already exploited to the (moderately) polar fraction of several complex matrices, such as essential oils and foodstuffs, guaranteeing a broad and reliable untargeted chemical profile [ 37 , 38 ]. However, an accurate metabolite quantification in direct infusion ESI FT-ICR MS is hampered due to possible ion-suppression effects and signal response disparities.…”
Section: Resultsmentioning
confidence: 99%